Multilevel Analysis : Techniques and Applications - Hox, Joop J; Moerbeek, Mirjam; van de Schoot, Rens (New York : Routledge/Taylor & Francis, 2018)
The book also includes advanced extensions, making it useful as both an introduction for students and as a reference for researchers. Basic models and examples are discussed in nontechnical terms with an emphasis on understanding the methodological and statistical issues involved in using these models. The estimation and interpretation of multilevel models is demonstrated using realistic examples from various disciplines including psychology, education, public health, and sociology. Readers are introduced to a general framework on multilevel modeling which covers both observed and latent variables in the same model, while most other books focus on observed variables. In addition, Bayesian estimation is introduced and applied using accessible software.
Includes appendix,references and index.
Keywords: Multilevel analysis; Survival analysis; Meta-analysis .